2004
DOI: 10.1103/physrevlett.93.160802
|View full text |Cite
|
Sign up to set email alerts
|

Push-Pull Optical Pumping of Pure Superposition States

Abstract: A new optical pumping method, "push-pull pumping," can produce very nearly pure, coherent superposition states between the initial and the final sublevels of the important field-independent 0-0 clock resonance of alkali-metal atoms. The key requirement for push-pull pumping is the use of D1 resonant light which alternates between left and right circular polarization at the Bohr frequency of the state. The new pumping method works for a wide range of conditions, including atomic beams with almost no collisions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
129
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(134 citation statements)
references
References 18 publications
2
129
0
Order By: Relevance
“…In the case of circularly polarized light fields, for example, this restriction leads to a significant reduction of CPT resonance amplitude since a large fraction of the atomic population becomes trapped in the "end" Zeeman states with the maximum value of the angular momentum (m F = F or m F = −F ) and not in the desired magnetic-field-insensitive states with m F = 0 [4]. To mitigate this problem, a variety of CPT schemes [5][6][7][8] as well as related coherent resonances [9][10][11] were proposed and studied by different groups.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of circularly polarized light fields, for example, this restriction leads to a significant reduction of CPT resonance amplitude since a large fraction of the atomic population becomes trapped in the "end" Zeeman states with the maximum value of the angular momentum (m F = F or m F = −F ) and not in the desired magnetic-field-insensitive states with m F = 0 [4]. To mitigate this problem, a variety of CPT schemes [5][6][7][8] as well as related coherent resonances [9][10][11] were proposed and studied by different groups.…”
Section: Introductionmentioning
confidence: 99%
“…The original proposal of the pushpull optical pumping technique [13] aimed at increasing the contrast of the magnetically insensitive transitions in atomic clocks by polarization modulation at the clock (i.e., hyperfine transition) frequency. The method has been demonstrated for the clock transition in rubidium [14], potassium [15], and cesium [16].…”
mentioning
confidence: 99%
“…This is why the clock transition cannot be observed with lin lin polarizations [7,9]. It has been shown that counter-rotating circular polarizations are efficient if one of the two circularly polarized beam is phase delayed by π relative to the other [10][11][12], or equivalently by linearly and orthogonally polarized beams [13]. Another possibility is to use a beam with alternating opposite circular polarizations [14].…”
Section: Introductionmentioning
confidence: 99%